Building Lptp Vpn Network and User Management Using Fuzzy Logic Based on Age and Utilization of The Dude for Network Monitoring - Fakhri Fakhlur Rahman; Sahari; Riska Robianto (Jurnal KomtekInfo, 2020)
This study aims to build a VPN network, develop the use of The Dude as network monitoring and user management of bandwidth sharing using fuzzy logic and using MICROTIC ROUTERBOARD as process controller. The benefit of developing this tool is to facilitate the admin or business owner in the process of monitoring and monitoring on hotspots. This research was conducted by designing, making and implementing system components which include routerboard as process controller, access point as 2.4Ghz signal transmitter, The Dude application as network monitoring and user management as well as VPN as connecting media from public network to local hotspot network. The results of this study indicate that the tools made can function well and are developed on a larger scale.